PELATIHAN ECOPRINT BAGI KADER PKK DI DESA TEGALWERU,KECAMATAN DAU,KABUPATEN MALANG - Alifiulahtin Utaminingsih; Wike Wike (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
Some one that have entrepreneurship spirit is some that do creatively and inovatively. Entrepreneur have characteristic improve skills, confidence have good self determination or locus of control, risk taker and look at change is chance for member of PKK in Tegalweri village. Sub District Dau, Malang Distric there are farming ecologies so many leafs and flowers  from any plants that can be use to make ecoprint batik models. Based on this condition so held  trainning of batik ecoprint to increace skill for member of PKK productive age in Tegalweru village that  economic creative based through ecoprint batik trainning to create  new women entrepreneur in order to increase family economic.